The Effect of Problem Solving Skills Training on Emotional Intelligence of Nursing Students of Shiraz (2008) - Sara Shahbazi; Maryam Hazrati; Marzieh Moattari; Mohammad Heidari (مجله ایرانی آموزش در علوم پزشکی, 2012)
Introduction: Problem solving is an important skill for living in nowadays world. Due to their professional responsibility and occupation in a complicated therapeutic environment, nurses should be skillful enough for problem solving in order to handle them. Therefore, this study was performed to determine the effect of problem solving course on nursing students' emotional intelligence of Shiraz University of Medical Sciences in year 2008. Methods: This quasi-experimental study was performed on 43 senior nursing students of Shiraz University of Medical Sciences. Primarily students were asked to complete questionnaires of demographic data and “BarOn" standard test for emotional intelligence evaluation. Then, the participants were randomly divided into two groups of experimental (N=20) and control (N=23). Then, 6 sessions of problem solving course based on D'zurilla and Goldfride social problem solving protocol, was performed for students of experimental group. Data was analyzed through statistical tests of Mann Whitney, Wilcoxon, Friedman’s test, and Pearson correlation Coefficient. Results: Standardization of emotional intelligence scores among students of experiment group showed a statistically significant difference for these scores achieved immediately (105.87±9.82) and 2 months after intervention (109.44±9.56) compared to the one before intervention (101.22±10.93) (p<0.01). The mean score of problem solving skill among students of experiment group showed also a statistically significant difference comparing the scores achieved immediately after intervention (8.31±77.75) and 2 months after that (8.00±78.75) to that of before intervention (11.95±71.35) (p<0.01). This is while control group showed no statistically significant difference considering these variables. Only 20 percent of students enjoyed a high emotional intelligence before intervention, while this increased to 40 percent of high intelligence and 10 percent of very high emotional intelligence 2 months after intervention. Conclusion: Problem solving skills lead to promotion of emotional intelligence among students of experiment group compared to control group. This result was stable not only immediately after intervention but also after two months. Therefore problem solving education in various nursing domains such as education, research, management and clinic, is recommended.